Improved ELISA for linoleate-derived diols in human plasma utilizing a polyHRP-based secondary tracer. Issue 18 (28th April 2022) - Singh, Nalin; Li, Dongyang; McReynolds, Cindy B.; Morisseau, Christophe; Hammock, Bruce D.
Abstract : A highly sensitive biotinylated IgG–streptavidin-polyHRP label-based ELISA for detection of linoleic acid-derived diols in human plasma. Abstract : Dihydroxyoctadecenoic acids (DiHOMEs) are cytochrome P450 pathway-derived metabolites of linoleic acid, a highly abundant dietary fatty acid. They serve thermogenic functions at low concentrations but, at high concentrations, are involved in proinflammatory and deleterious outcomes in a wide range of pathologies. Hence, the development of a reliable analytical method is critical to elucidate their potential as biomarkers of health, and enzyme-linked immunoassay (ELISA)-based approaches offer unique benefits as alternatives to traditional liquid chromatography-tandem mass spectrometry (LC-MS/MS) systems. Accordingly, an earlier ELISA for DiHOMEs was dramatically improved employing new secondary tracers and geared towards use in human plasma, a universal matrix in biomedical applications, as well as urine. Three ELISA formats, two utilizing polyHRP-based secondary labels for signal amplification, were compared. The best format involved a biotinylated detection antibody and a polyHRP-conjugated streptavidin tracer. Assay detectability was enhanced 20-fold, relative to the original immunoassay, and performance assessments validated precision, selectivity, and robustness. Fast and easy extraction-clean up steps yielded high analytical recovery and permitted the assay to operate in moderate concentrations (up to 20%) of plasma, expanding its practical relevance. Finally, the ELISA was applied towards detection of DiHOMEs in clinical samples and authenticated with complementary LC-MS/MS analysis. Hence, the method provides a valuable analytical tool to investigate the diverse and extensive roles of DiHOMEs in regulatory biology.